Development of In-Bi-Sn Composite Metal Inks with Modified Properties for 3D Printed Electronics - Koo, Bonjin; Dang, Hyun Woo; Yoo, In-Kyu; Moon, Myung Woon; Yang, Yong Suk (AMER SCIENTIFIC PUBLISHERS, 2017)
In-Bi-Sn composite metals are an alloy-particle mixture with low melting temperatures and high conductivity. In this study, they were prepared by blending liquid Field's metal, an In-Bi-Sn eutectic alloy, with Cu flakes. The characteristics and modified properties of the fabricated composite metals were analyzed by comparative studies of their thermal, rheological, and electrical behaviors. The results suggest that the amount of added Cu flake plays an important role in the growth of viscosity and reduction of resistivity. The non-Newtonian behavior of the melted composite metal was investigated using a rheometer, and the tendency of viscosity in terms of shear rate and time was found to be enhanced by introducing Cu flakes. The resistivity of the alloy-particle mixture was reduced from 52.40 mu Omega.cm to 48.07 mu Omega.cm with 15 wt.% of Cu flake insertion. The applicability of the In-Bi-Sn composite metal as a liquid metal ink for 3D metal printing was demonstrated by generating raster patterns using a hot-melt-dispensing based 3D printer and a nozzle with a diameter of 300 mu m.